Moving with the in-crowd: Cooperation and interpersonal entrainment in in- vs. out- groups - Cross, L. *; Turgeon, M.; Atherton, G. * (Springer Verlag (Germany), 2019)
Interpersonal entrainment or moving together in time, has been shown to cultivate pro-social behaviours amongst those who take part. Converging evidence suggests that its pro-social effects may be intertwined with how we classify ourselves and our co-actor in group terms. However, it is not currently clear if a well-established collective identity, such as national identities, influences entrainment’s effects on our actual behaviours, such as cooperation. The current studies tested whether greater cooperation was seen following synchronous versus asynchronous movements when people were moving with somebody of the same vs. a different nationality. As expected, results showed greater cooperation following synchronous vs asynchronous movements amongst people of different socio-cultural backgrounds, but not amongst those with a common socio-cultural background. Potential explanations for these results are explored, suggesting that entrainment and its social effects may be modulated by our group identities.